2018
DOI: 10.1111/jvh.13013
|View full text |Cite
|
Sign up to set email alerts
|

Australia on track to achieve WHO HCV elimination targets following rapid initial DAA treatment uptake: A modelling study

Abstract: Summary Subsidized direct‐acting antiviral (DAA) treatment recently became available to all adults living with chronic hepatitis C virus (HCV) in Australia. Based on rapid uptake (32 600 people initiated DAA in 2016), we estimated the impact on HCV epidemiology and mortality in Australia and determined if Australia can meet the WHO HCV elimination targets by 2030. Using a mathematical model, we simulated pessimistic, intermediate and optimistic DAA treatment scenarios in Australia over 2016‐2030. We assumed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 32 publications
(48 reference statements)
3
72
1
Order By: Relevance
“…To reach the WHO elimination targets of 80% of people with hepatitis C being treated and incidence being reduced to 80% of the 2015 level by 2030, the number of hepatitis C‐exposed people identified and tested needs to be increased by at least 50%. Our finding contrasts with previous modelling which suggested that Australia was on track to achieving the 2030 elimination targets; however, the earlier projection was predicated on treatment numbers being maintained at current levels. In our study, we additionally modelled the hepatitis C care cascade, and found that treatment numbers will decline to fewer than required to meet the elimination targets unless testing is increased.…”
Section: Discussioncontrasting
confidence: 99%
“…To reach the WHO elimination targets of 80% of people with hepatitis C being treated and incidence being reduced to 80% of the 2015 level by 2030, the number of hepatitis C‐exposed people identified and tested needs to be increased by at least 50%. Our finding contrasts with previous modelling which suggested that Australia was on track to achieving the 2030 elimination targets; however, the earlier projection was predicated on treatment numbers being maintained at current levels. In our study, we additionally modelled the hepatitis C care cascade, and found that treatment numbers will decline to fewer than required to meet the elimination targets unless testing is increased.…”
Section: Discussioncontrasting
confidence: 99%
“…368 Australia has made major progress in tackling bloodborne viruses and sexually transmissible infections over the past two decades. At the time of writing, the country could eliminate hepatitis C by 2030, and WHO reports 369 that hepatitis B prevalence in children is less than 1%. The current health workforce needs to increase to promote primary providers' awareness and knowledge of hepatitis B and C, and an increase in support, training, and mentorship for health-care professionals is needed to ensure successful testing, management, and treatment in primary health care.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…The status quo assumed continuation of the current situation in the NSW prisons: a starting total prisoner population in 2017 of 14 683, including 7862 PWID, 3847 of whom were actively injecting at any one time (as reported ); 1400 individuals receiving OST at any one time from 2006 onwards ; and 200 DAA treatments per year from 2014 to 2016, 700 in 2016 and 1000 in 2017, again reflecting the actual scale‐up of DAA treatment in the NSW prisons. The impact of further scale‐up of DAA treatment provision, improved access to OST (implying both timely provision upon incarceration and suitable dosing, as well as increased numbers initiated on OST), introduction of NSP and also the expected reduction in community HCV prevalence due to the national DAA treatment rollout, were then tested (Table ) . Various combined treatment and prevention scenarios were then simulated based on these strategies (Table ).…”
Section: Projection Scenariosmentioning
confidence: 99%
“… Derived from NSW estimates and projections . HCV = hepatitis C virus; DAA = direct‐acting antiviral; NSP = needle and syringe programme; OST = opiate substitution treatment.…”
Section: Projection Scenariosmentioning
confidence: 99%